PEMBENTUKAN KARAKTER ANAK MELALUI PERMAINAN TRADISIONAL CIM-CIMAN - Fauzi Fauzi (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2016)
This research aimed in describing and reconstructing the existence of Cim-ciman as traditional child game, and also on founding the substance role of, in developing and constructing the character of child in early age. This research conducted in the district of Banyumas in Central Java and used qualitative research approach. Data collection used participation observation technique which is supported by observation sheet as observation focus standard. The data was analysed through Miles and Huberman model of qualitative analysis technique. The result showed that the game of Cim-ciman can be applied on practicing and stimulating child development in various aspect as holistic and integrative point of view, either motoric physical aspect, language, cognitive, social, emotional, and moral. Besides that, it can be used in growing and forming cultural values and constructing child character, for example, honesty, discipline, creativity, integrity, responsibility, social solidarity, hard work, spirit, achievement appreciation, friendship or communication, peace keeping, and dialogue. In this case, the reconstruction and revitalization of child traditional game (dolanan for child), that are spread in all parts of Indonesia with their cultural uniqueness,are needed, and then to be made as early education menu.